Accumulation of marine litter in cold-water coral habitats: A comparative study of two Irish Special Areas of Conservation, NE Atlantic. (July 2022) - Appah, J.K.M.; Killeen, O.; Lim, A.; O'Riordan, R.; O'Reilly, L.; Wheeler, A.J.
Abstract: Cold-water corals (CWCs) have come under threat from anthropogenic activities such as fishing despite their ecological significance as biodiversity hotspots and as such are being protected in Europe under the EU Habitats Directive with some designated as Special Areas of Conservation (SACs). This study maps the distribution and sources of marine litter in CWC habitats in two SACs on the Irish margin. Data were collected with remotely operated vehicle in the SACs. The density, abundance and composition of litter were assessed, with differences observed between the two sites. The regional morphology influences the distribution of litter in the SACs, with CWC reefs and rock exposures trapping more marine litter. Fishing gear (80.7%) and plastics (55.1%) were commonly found. The observed fisheries-derived litter in the SACs exceed global averages of 10–20% fishing gear, suggesting the SACs appear to offer limited protection to the coral habitats with respect to marine litter. Highlights: Seabed morphology and cold-water coral presence affect the distribution of marine litter. Marine litter can affect the growth and survival of cold-water corals. Special Areas of Conservation (SACs) closures do not necessarily offer protection against the entry of litter. Fishing related litter is more than 20% in the Porcupine Bank Canyon SAC and the Belgica Mound Province SAC. Litter accumulation is higher on a relatively flattened surface than along a steep slope.